2004
DOI: 10.1086/502319
|View full text |Cite
|
Sign up to set email alerts
|

Improving Influenza Immunization Rates Among Healthcare Workers Caring for High-Risk Pediatric Patients

Abstract: Despite delayed distribution of influenza vaccine during the 2000-2001 season, immunization rates at 7 hospitals and among HCWs in high-risk units exceeded the National Association of Children's Hospitals and Related Institutions goal of 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 28 publications
2
33
1
1
Order By: Relevance
“…Low vaccination coverage among HCWs has been observed not only in Germany but also in several other European and non-European countries [30][31][32][33][34][35][36][37][38][39]. assessed by Blank et al was similar to that found in our study [20], vaccination coverage in the target groups diverged significantly from our findings.…”
Section: Discussionsupporting
confidence: 85%
“…Low vaccination coverage among HCWs has been observed not only in Germany but also in several other European and non-European countries [30][31][32][33][34][35][36][37][38][39]. assessed by Blank et al was similar to that found in our study [20], vaccination coverage in the target groups diverged significantly from our findings.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of reviewed studies reported self-protection to be the most important reason for vaccination. In terms of influenza, as expected, HCW self-protection was a highly significant predictor of vaccination for seasonal influenza, which other studies [37][38] have noted. Our finding for support for the obligation to be vaccinated against influenza (79.4%) is higher than that reported by Seale 39 who found only 46.8% of respondents in a survey of two tertiary hospitals in Sydney supported a policy of compulsory influenza vaccination for HCWs.…”
Section: Discussionsupporting
confidence: 84%
“…Many worldwide programs are introduced in order to increase the vaccination rates in health personel but surprisingly, their is a resistance. In studies performed in various countries, the influenza vaccination rates in health personel was below 50% [17][18][19][20][21][22]. In our study the rate of having been vaccinated in any season was 58.5% and the ones that were vaccinated this season were only half of these.…”
Section: Discussioncontrasting
confidence: 51%